Investigation of surface acoustic waves on LiNbO3, quartz, and LiTaO3 by laser probing - Holm, Andreas; Stürzer, Quirin; Xu, Y.; Weigel, Robert (Microelectronic Engineering, 1996)
Laser probing for the investigation of surface acoustic wave (SAW) devices has been established on account of some important advantages. Nondestructive testing and phase preserved imaging of the wave field yield valuable information for evaluation of the material data. In the following, results from high accuracy phase velocity measurements on SAW-cut crystals, e.g. 128°-YX-LiNbO3 and ST-quartz will be presented. Moreover it is shown the detection of leaky surface acoustic waves (LSAW) on 36°-YX-LiTaO3, which is a wave mainly polarized parallel to the surface plane. However, high sensitivity of the measurement system enables the detection of the weak bending perpendicular to the surface.
elib2cris::1512001600,holm1996a
Keywords: surface; acoustic; wave; LiNbO3; laser; probing; SAW